Data Mining Approach On Assessing The Human Motion Balancing Mechanisms - Kogulan, Letchumanan (Universiti Sains Malaysia, 2017)
Data mining approach can be described as the process of converting a big and uncontrolled size of data into a more simple and useful form data. This project uses data mining approach to access human stability when a motion involved. In this project, we involve the activities perform a normal human being to find out the perfect posture for them to do that activity. Data mining comprises of few stages which are data collection, data preprocessing, data processing and knowledge discovery. Data are analysed by using a group of people consist of 10 people from different age and physical appearance. By applying data mining approach to human motion, we can avoid injuries and take proper safety precautions.